Steatocrit Value in New-Born Babies - Johnwan Usman; Irfan Abdullah; Muhazar Muhazar; Atan Baas Sinuhaji; A. H. Sutanto (Indonesian Pediatric Society, 1995)
A prospective study on steatocrit value in full-term or preterm newborn babies of 2 days of age in Dr. Pimgadi Hospital, Medan is reported. This study was conducted from December 7, 1992, to February 7, 1993; there were 72 newborn babies (37 males and 35 females). The body weight was> 2500 gin 60 babies and s. 2500 gin 12 babies. The median steatocrit value in babies with body weight of> 2500 g was 9%, and it was 32% in babies less than 2500 g of body weight. The proportion of babies with > 25% steatocrit value was larger in babies less than 2500 g than that in 2500 g by the diet patterns of breast milk, breast milk and milk formula, milk formula. The proportion of babies with < 25% steatocrit value was higher in babies with body weight of< 2500 g than that in babies > 2500 g for those who had either breast milk, breast milk and milk formula or milk formula. There was significant difference (p<0,05) in the steatocrit levels between babies with the body weight of > 2500 g and those who had body weight of â‰¤ 2500 g.